Maestros in America: Conductors in the 21st Century - Sharpe, Roderick L.; Stierman, Jeanne Koekkoek (Rowman & Littlefield Publishers, 2008)
Maestros in America: Conductors in the 21st Century provides short biographical and critical essays of over 100 American conductors-and conductors in America-in the twenty-first century. Roderick L. Sharpe and Jeanne Koekkoek Stierman made their selections based on three categories of persons: American-born; naturalized US citizens; and foreign conductors holding a permanent appointment in the US. In addition, all individuals included had to have been active as conductors at the start of the new millennium. These criteria allowed the authors to incorporate up-and-comers as well as those more established, offering an extensive cross-section of the upper echelons of the conducting profession focused on the present, recent past, and future. Each entry is a biographical essay containing essential facts of the conductor's life and work, as well as assessment and commentary gleaned from articles, interviews, reviews, and, in some cases, personal observation. The entries conclude with the conductor's website, a list of further reading, and selected recordings. These sketches of currently or recently practicing conductors provide insight into the state of orchestral music-making in the US as it is, has been, and may become, highlighting the efforts these conductors made to ensure its survival. Complete with two appendixes and an index, this important reference will be beneficial to music students and faculty, reference librarians, orchestral administrators, and music lovers alike.